2022
DOI: 10.1002/app.52851
|View full text |Cite
|
Sign up to set email alerts
|

Shear and elongational rheometry for determination of spinnability window of polymer solutions in solution blow spinning

Abstract: Recently, processes for stable and efficient production of polymeric nano-and submicron fibrous materials, like solution blow spinning, have developed rapidly. However, the application of new polymers, synthetic or natural, for the fabrication of innovative fibrous materials still requires a trial-and-error approach to determine the spinnability window of polymer concentration in the solution. In this study, we investigated the use of shear and elongational rheometry to determine the spinnability window of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As observed in Fig. 5, these microfibers from elongated microbeads (Janus structure) with decreasing molar mass, which can be attributed to deficiencies in the viscous forces for this solution, indicating a lower geometric relaxation time for the solution [62,63]. On the other hand, in this result, the authors can see that with the increase of storage time for PCL solution an increasing number of beads appeared, as shown in Fig.…”
Section: Relationship Between Molar Mass and Morphology Of Fibrous St...mentioning
confidence: 61%
See 1 more Smart Citation
“…As observed in Fig. 5, these microfibers from elongated microbeads (Janus structure) with decreasing molar mass, which can be attributed to deficiencies in the viscous forces for this solution, indicating a lower geometric relaxation time for the solution [62,63]. On the other hand, in this result, the authors can see that with the increase of storage time for PCL solution an increasing number of beads appeared, as shown in Fig.…”
Section: Relationship Between Molar Mass and Morphology Of Fibrous St...mentioning
confidence: 61%
“…In this regime, the solution lacks the necessary viscous resistance to be deformed, resulting in the continuous jet breaking into droplets, resembling the electrospraying processes, as shown in Figure 5. In this context, it can be referenced that the viscoelastic behavior exhibits low relaxation times [44,59,62,63]. The analysis of variance (ANOVA) results presented in Table 3 revealed that the storage time of PCL solutions in acetic acid for up to 7 days had the most significant influence on the variation of fiber diameter, with a confidence level above 99.9%.…”
Section: Relationship Between Molar Mass and Morphology Of Fibrous St...mentioning
confidence: 94%
“…These results were consistent with our observation that the PCUU at 6 wt % concentration was too viscous for the ES process to be effective. If the solution was too diluted, then the polymer fiber broke up into droplets before reaching the collector due to the effects of surface tension and insufficient overlapping of polymer molecules to the critical polymer concentration . However, if the concentration of the solution was too high, then fibers could not be formed due to the high viscosity, which made it difficult to control the solution flow rate through the capillary …”
Section: Resultsmentioning
confidence: 99%
“…The most critical process parameters in blow spinning include polymer flow rate from the nozzle, compressed gas flow rate, nozzle diameter, nozzle-to-collector distance, and collector rotational speed [20,21]. Among the physicochemical parameters of the solution, the following are essential: polymer concentration, extensional viscosity, surface tension, and apparent viscosity [22]. The temperature and humidity in which blow spinning is carried out also affect its course.…”
Section: Introductionmentioning
confidence: 99%